Efficacy of eculizumab in refractory life‐threatening warm autoimmune hemolytic anemia associated with chronic myelomonocytic leukemia. Issue 12 (17th August 2020) - Gauchy, Anne‐Cécile; Hentzien, Maxime; Wynckel, Alain; de Marcellus, Victoire; Rodier, Cyrielle; Delmer, Alain; Quinquenel, Anne
Abstract: Eculizumab may be considered as an emergency therapeutic option in refractory life‐threatening warm autoimmune hemolytic anemia especially if direct antiglobulin test is positive for both IgG and C3d and after failure of all conventional treatments. Abstract : Eculizumab may be considered as an emergency therapeutic option in refractory life‐threatening warm autoimmune hemolytic anemia especially if direct antiglobulin test is positive for both IgG and C3d and after failure of all conventional treatments.